Deep sequencing and variant analysis of an Italian pathogenic field strain of equine infectious anaemia virus. Issue 6 (15th March 2017) - Cappelli, K.; Cook, R. F.; Stefanetti, V.; Passamonti, F.; Autorino, G. L.; Scicluna, M. T.; Coletti, M.; Verini Supplizi, A.; Capomaccio, S.
Summary: Equine infectious anaemia virus (EIAV) is a lentivirus with an almost worldwide distribution that causes persistent infections in equids. Technical limitations have restricted genetic analysis of EIAV field isolates predominantly to gag sequences resulting in very little published information concerning the extent of inter‐strain variation in pol, env and the three ancillary open reading frames (ORFs). Here, we describe the use of long‐range PCR in conjunction with next‐generation sequencing (NGS) for rapid molecular characterization of all viral ORFs and known transcription factor binding motifs within the long terminal repeat of two EIAV isolates from the 2006 Italian outbreak. These isolates were from foals believed to have been exposed to the same source material but with different clinical histories: one died 53 days post‐infection (SA) while the other (DE) survived 5 months despite experiencing multiple febrile episodes. Nucleotide sequence identity between the isolates was 99.358% confirming infection with the same EIAV strain with most differences comprising single nucleotide polymorphisms in env and the second exon of rev . Although the synonymous:non‐synonymous nucleotide substitution ratio was approximately 2:1 in gag and pol, the situation is reversed in env and ORF3 suggesting these sequences are subjected to host‐mediated selective pressure. EIAV proviral quasispecies complexity in vivo has not been extensively investigated; however, analysis suggests it was relatively low in SA at the time of death. These results highlight advantages of NGS for molecular characterization of EIAV namely it avoids potential artefacts generated by traditional composite sequencing strategies and can provide information about viral quasispecies complexity.